Assessment of the Persistence of Anti SARS-Cov2 Igg Antibody Over a Period of Six Months Among Industrial Workers (Medical Forum Monthly, 2023)
Objective: To assess the presence of anti-(SARS-CoV-2) antibodies among industrial workers in Pakistan and persistence of the antibodies over a period of 6 months and compare the levels of IgG antibodies in asymptomatic and symptomatic individuals.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the National institute of Blood Diseases and Bone-marrow transplantation, Karachi from June 2020 to November 2020.Materials and Methods: Male industrial workers were included and testing for detection of COVID-19-IgG antibodies by ELISA technique was performed initially in June 2020 and then in the months of September and November of the same year.Results: Eighteen out of 36 male workers were positive for antibodies in June 2020 on baseline. Of those 18 individuals, 16 remained positive after a period of 3 months while 03 of them were still positive after a period of 06 Months. Among the borderline positive workers, two turned into positive after a period of 3 months while all of them became negative at the end of 06 months period.Conclusion: It is concluded that individuals exposed to SARS CoV-2 develop IgG antibodies which are higher in asymptomatic individuals and persist for more than 03 months in most of the individuals. These antibodies decline in a gradual manner quantitatively and fade away before the period of 06 months in majority of the individuals.